Dampak Positif dan Negatif Penggunaan Uang Elektronik di Dunia Pendidikan - Sosrowidigdo, Suryanto (Universitas Sebelas Maret, 2023)
This research aims to explore the use of electronic money in the world of education, as well as its positive and negative impacts. This research is a literature study from various studies discussing the use of electronic money in education. Data was retrieved via Google Scholar on the Publish or Perish (PoP) software. The search was carried out using the keywords